Impact Of Attitude On Adoption Of Telecommuting In Organizations In Penang - Ndubisi, Nelson Olunna (1998)
Today, human resource management and industrial relations literature is full with discussions concerning award restructuring and strategies designed to improve organisational effectiveness and efficiency. However, little attention has been directed towards the rapidly changing nature of organisations themselves and whetheror not organisations as we know them will survive the post industrial revolution.